SALES APPLICATION ON KEBAYA SCOUTS COMPANY USING MICROSOFT VISUAL BASIC 6.0 - Thoyib Januardi; Yulina Yulina,Skom, MMSi (Jurnal Sistem Informasi, 2008)
Scientific writing contains a simple program on computerization sales kebaya, using input goods through the production and sales process, which will then automatically stored in a database and display the output results will come out that will be received by the customer or purchaser as the invoice or receipt and view reports required by employers such kebaya. The process of inputting and sales of computerized this makes data processing more efficient and accurate and can provide information on existing inventory.